Livestock and poultry excrement fermentation production line - XIE HANGUO (2016)
The invention discloses a livestock and poultry excrement fermentation production line, which solves the problems of great work intensity, poor sanitary condition and the like in the existing livestock and poultry excrement fermentation process. According to the production line, a solid-liquid separating machine (5) is connected with a draining device (4) through a first lifting machine (7); the draining device (4) is connected with a fermentation tower (2) through a second lifting machine (3); the fermentation tower (2) is connected with a bagging discharging opening (10) and a second lifting machine (3) through a third lifting machine (11) and a material distributor (9). Therefore the livestock and poultry excrement fermentation production line has the advantages that the work intensity is low; the mechanization is realized; the automation level is high; meanwhile, safety and sanitation can also be ensured. 本发明公开了这样种畜禽粪便发酵生产线，为解决已有畜禽粪便发酵存在的劳动强度较大、卫生条件较差等不足，本发明采取所述固液分离机(5)通过笫提升机(7)与滤干装置(4)连接，滤干装置(4)通过笫二提升机(3